2016
DOI: 10.4236/ojemd.2016.63017
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Thyroid Hormones in Patients with Chronic Hepatitis C Virus Infection

Abstract: Objective: There are clinical and laboratory associations between thyroid and liver diseases. Hepatitis C virus (HCV) is known to be responsible for both hepatic and extrahepatic diseases. The most frequent and clinically important endocrine extrahepatic diseases are thyroid disorders and type 2 diabetes mellitus. We aim to study the relationship between the serum level of thyroid hormones (THs) and the severity of liver disease in patients with chronic hepatitis C virus (CHC) infection. Methods: 60 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…The results of the present study [ Table 2 ] showed a statistically highly significant increase in TSH levels in all cirrhosis patients compared to healthy controls ( P < 0.0001). El-Feki and Abdalla[ 17 ] concluded the same results. Antonelli et al .…”
Section: Discussionsupporting
confidence: 61%
“…The results of the present study [ Table 2 ] showed a statistically highly significant increase in TSH levels in all cirrhosis patients compared to healthy controls ( P < 0.0001). El-Feki and Abdalla[ 17 ] concluded the same results. Antonelli et al .…”
Section: Discussionsupporting
confidence: 61%
“…Recently an association between liver dysfunction and thyroid hormone has been elucidated in HCV patients [2830]. Besides these we have not determined thyroid autoimmunity related parameters like serums Tg-Ab and TPO-Ab and ultrasound echogenicity in our patients.…”
Section: Discussionmentioning
confidence: 80%
“…Limitations of this study are its cross-sectional nature, comparatively low number of male patients, serum FT 3 determination in a few patients, and incomplete medical information like liver enzyme and biopsy status. Recently an association between liver dysfunction and thyroid hormone has been elucidated in HCV patients [ 28 30 ]. Besides these we have not determined thyroid autoimmunity related parameters like serums Tg-Ab and TPO-Ab and ultrasound echogenicity in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…A similar male predominance among such patients has been reported previously by Ali et al who observed it to be 1.5:1 in the local population [ 11 ]. El-Feki et al in 2016 reported a similar male to female ratio of 1.5:1 among Egyptian patients with CLD [ 19 ]. Mansour-Ghanaei et al in 2012 reported a male to female ratio of 1.9:1 among CLD patients in Iran [ 15 ].…”
Section: Discussionmentioning
confidence: 99%